Classification of two-dimensional Jordan algebras over R - Hussein, Ahmed Houida Mohammed; Ural, Bekbaev; Rakhimov, Isamiddin Sattarovich (Institute for Mathematical Research, Universiti Putra Malaysia, 2018)
In the paper we describe all (not necessarily commutative) Jordan algebra structures on a two-dimensional vector space over R in terms of their matrices of structure constants.